2010
DOI: 10.1177/1352458509357063
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in neuronal gene expression profiles in response to experimental demyelination and axonal transection

Abstract: The main pathological features of multiple sclerosis, demyelination and axonal transection, are considered to cause reversible and irreversible neurological deficits, respectively. This study aimed to separately analyze the effects of these pathological hallmarks on neuronal gene expression in experimental paradigms. The pontocerebellar pathway was targeted with either lysolecithin-induced chemical demyelination or a complete pathway transection (axonal transection) in rats. Transcriptional changes in the pont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Transcriptional changes often underlie differences in cellular function, and gene expression profiling has been undertaken in experimental chemical demyelinating lesions (Lovas et al, 2010) as well as in MS to examine neuronal gene changes (Dutta et al, 2007Schirmer et al, 2019). took advantage of the variable degree of demyelination within individual MS hippocampi to assess the influence of demyelination on gene expression.…”
Section: Neuronal Transcriptional Responses To Demyelinationmentioning
confidence: 99%
“…Transcriptional changes often underlie differences in cellular function, and gene expression profiling has been undertaken in experimental chemical demyelinating lesions (Lovas et al, 2010) as well as in MS to examine neuronal gene changes (Dutta et al, 2007Schirmer et al, 2019). took advantage of the variable degree of demyelination within individual MS hippocampi to assess the influence of demyelination on gene expression.…”
Section: Neuronal Transcriptional Responses To Demyelinationmentioning
confidence: 99%
“…Furthermore, a study reported that ATF3 was upregulated in the inflamed spinal cord of animals with constriction injury of the sciatic nerve [ 35 ] and in the pontine nuclei following demyelination of the pontocerebellar tract. In a patient with Marburg's variant of multiple sclerosis, ATF3 was found in neurons within the pontine nuclei and neocortex [ 36 ]. A caveat is that the extent of axonal injury in such cases of demyelination remains unknown.…”
Section: P Rotective Effects Of Activating Transcription Famentioning
confidence: 99%
“…Pontocerebellar neurons show a prolonged (weeks) upregulation of ATF3 after axotomy (Lovas et al, 2010). The same applies to dopaminergic neurons in the substantia nigra pars compacta (Song et al, 2008), and olivocerebellar neurons following axotomy within the cerebellum (our unpublished observations).…”
Section: Atf3 In Normal and Injured Neuronsmentioning
confidence: 99%
“…In a patient with Marburg’s variant of multiple sclerosis ATF3 was found in neurons within the pontine nuclei and neocortex (Lovas et al, 2010). A caveat is that the extent of axonal injury in such cases of demyelination remains unknown.…”
Section: Atf3 In Normal and Injured Neuronsmentioning
confidence: 99%